Orientation and Position of Fish Affects Recovery Time from Electrosedation. Issue 4 (23rd June 2015) - Rous, Andrew M.; Forrest, Alexandra; McKittrick, Elisabeth Hart; Letterio, George; Roszell, Jordan; Wright, Taylor; Cooke, Steven J.
Abstract: Commercially available electrosedation apparatuses (e.g., the Smith‐Root Portable Electroanesthesia System [PES]) are growing in popularity within the fisheries research community. This technology can be used to immobilize fish rapidly and does not require a withdrawal period before fish are released. A number of studies examined how various settings (e.g., duration, frequency, voltage) influence the performance of the PES for fish sedation, but comparatively less is known about the role of fish orientation and position on the efficacy of electrosedation within the PES. We compared recovery times of Bluegill Lepomis macrochirus upon manipulation of three variables: orientation of fish, electric field size (i.e., spacing between the anode and cathode), and fish proximity relative to the anode. Fish were individually exposed to pulsed DC with a standardized frequency (100 Hz), voltage (90 V), and shock duration (3 s). Full recovery time was significantly longer for fish oriented at horizontal angles (0° and 180°) than at acute angles (45° and 135°). Significant interactions were found between orientation and electrode spacing, as well as between orientation and fish proximity. These findings are pertinent to researchers in the field looking to optimize recovery time for a quick release after surgery, tagging, or any other time fish sedation is required.